2020
DOI: 10.3389/fphys.2020.00946
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Course of Changes in Muscle Mass, Architecture and Power During 6 Weeks of Plyometric Training

Abstract: To investigate the time-course of changes in knee-extensors muscle mass, architecture and function in response to plyometric training (PLT) performed on a novel training device, the Tramp-Trainer. This machine consists in a trampoline connected to an inclined sledge which allows the performance of repeated jumps while the subject is sitting on a chair. Methods: Eight healthy males (173.6 ± 4.7 cm, 69.7 ± 13.5 kg, 25.3 ± 4.6 years) underwent 6 weeks of bilateral PLT on the tramp-trainer machine. Training was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 70 publications
3
25
0
1
Order By: Relevance
“…However, in this study, PCSA did not change with concurrent training focused on APL (ES = −0.07), illustrating that radial muscle hypertrophy was negligible in elite athletes. Similarly, it was previously observed that pennation angle increased in untrained individuals with plyometric [+6%; (Monti et al, 2020)] and eccentric training +5-21%; (Blazevich et al, 2007;Franchi et al, 2014)], however, pennation angle decreased in the rowers in our study after concurrent training with APL (−2 • , −9 ± 15%, ES = −0.71), similar to observations in elite athletes after sprint and jump training [−3 • ; (Blazevich et al, 2003)]. Therefore, adaptations in muscle morphology are likely different in elite athletes compared to untrained individuals.…”
Section: Training-induced Adaptations In Muscle Morphology and Performancesupporting
confidence: 64%
“…However, in this study, PCSA did not change with concurrent training focused on APL (ES = −0.07), illustrating that radial muscle hypertrophy was negligible in elite athletes. Similarly, it was previously observed that pennation angle increased in untrained individuals with plyometric [+6%; (Monti et al, 2020)] and eccentric training +5-21%; (Blazevich et al, 2007;Franchi et al, 2014)], however, pennation angle decreased in the rowers in our study after concurrent training with APL (−2 • , −9 ± 15%, ES = −0.71), similar to observations in elite athletes after sprint and jump training [−3 • ; (Blazevich et al, 2003)]. Therefore, adaptations in muscle morphology are likely different in elite athletes compared to untrained individuals.…”
Section: Training-induced Adaptations In Muscle Morphology and Performancesupporting
confidence: 64%
“…In this study, although we were not able to assess whole-body muscle mass as reported in a number of HIIT studies (Boereboom et al, 2016;Brown et al, 2018;Marcos-Pardo et al, 2019;Scott et al, 2019), we saw no change in VL MT, reported to be representative of muscle mass (Franchi et al, 2018) or VL FL (Randhawa and Wakeling, 2015) in any of the groups. We did however observe an increase in PA in both HIIT groups which is thought to represent an increase in cross sectional area and associated force and contractile capability (Lee et al, 2015;Monti et al, 2020). Whilst improvements in muscle PA have been shown following training modalities commonly associated with hypertrophy and strength gains, e.g., resistance and plyometric exercise training (Monti et al, 2020), the impact of HIIT on PA has been less well-studied.…”
Section: Discussionmentioning
confidence: 60%
“…We did however observe an increase in PA in both HIIT groups which is thought to represent an increase in cross sectional area and associated force and contractile capability (Lee et al, 2015;Monti et al, 2020). Whilst improvements in muscle PA have been shown following training modalities commonly associated with hypertrophy and strength gains, e.g., resistance and plyometric exercise training (Monti et al, 2020), the impact of HIIT on PA has been less well-studied.…”
Section: Discussionmentioning
confidence: 60%
“…We acquired pictures at rest while the participants laid in a supine position on their back. A guide was mounted to the leg in order to keep the same transversal path 19 . We took pictures of both muscles at 33 and 50% of the distance between the trochanter major and the lateral femur condyle.…”
Section: Methodsmentioning
confidence: 99%